Modern interpretations of Shakespearian Tragedies - Yelik Nursultan, Abzalbek Maxim, Anar Yerkebay, (Opción, 2019)
The purpose of the research is to consider modern interpretationsof Shakespearian tragedies by Kazakh, Russian and Georgian theatredirectors. The wise combination of different stage readings – theEastern and European ones – served as a basis of the article effectiveresearch method. As a result, each theatre strives to comprehend thehigh poetry and inherent lyricism of Shakespearian drama and, at thesame time, to enhance the social agency and significance of the tragiccharacter. In conclusion, a theatre production may acquire nationaltints in order to be better understood by the audience.